Peningkatan Pengetahuan Mengenai Faktor – Faktor yang Mempengaruhi Kejadian Bayi Berat Lahir Rendah pada Ibu Hamil - Eka Fitriyanti; Eka Widyastuti, Deny; Desy Widyatutik; Arista Apriani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
Infant Mortality Rate is the death rate that occurs after birth until the baby is exactly one year old. The Infant Mortality Rate (IMR) is an important indicator in reflecting the state of public health because it can describe the general health of the population. IMR is a health indicator which is included in one of the SDG's targets which is a continuation of the MDGS program which ended in 2015. The causes of low birth weight babies can come from various factors such as maternal, fetal, placental and environmental factors. Perinatal mortality in low birth weight babies babies is eight times greater than in normal babies. Low birth weight babies can cause both short and long term problems. The aim of carrying out this activity is that it is hoped that there will be an increase in knowledge regarding the factors that influence the incidence of low birth weight babies in pregnant women. This community service activity is carried out in 3 different activities, namely Activity I measuring mothers' knowledge regarding the factors that influence the incidence of low birth weight babies, Activity 2 providing health education to mothers regarding the factors that influence the incidence of low birth weight babies and activity 3 measuring knowledge regarding factors that influence the incidence of low birth weight babies. The results of this community service activity were obtained after being given education using posters, all pregnant women were able to explain the meaning and factors that cause low birth weight babies.   ABSTRAK                 Angka Kematian Bayi (Infant Mortality Rate) adalah kematian yang terjadi saat setelah lahir sampai bayi berusia tepat satu tahun. Angka Kematian Bayi (AKB) merupakan salah satu indikator penting dalam mencerminkan keadaan derajat kesehatan masyarakat karena dapat menggambarkan kesehatan penduduk secara umum. AKB merupakan indikator kesehatan yang termasuk didalam salah satu target SDG’s yang merupakan kelanjutan dari program MDGS yang telah berakhir di tahun 2015. Penyebab BBLR dapat berasal dari berbagai faktor seperti faktor ibu, janin, plasenta dan lingkungan. Kematian perinatal pada bayi BBLR delapan kali lebih besar dibandingkan dengan bayi normal. BBLR dapat menyebabkan masalah baik jangka pendek maupun jangka panjang. Tujuan dilaksanakannya kegiatan ini adalah diharapkan terjadi Peningkatan Pengetahuan mengenai Faktor-Faktor yang mempengaruhi Kejadian BBLR pada Ibu Hamil. Kegiatan pengabdian kepada masyarakat ini dilaksanakan dalam 3 kegiatan yang berbeda, yaitu  Kegiatan I melakukan pengukuran pengetahuan ibu mengenai faktor-faktor yang mempengaruhi kejadian BBLR, Kegiatan 2 memberikan pendidikan kesehatan kepada ibu mengenai faktor-faktor yang mempengaruhi kejadian BBLR dan kegiatan 3 melakukan pengukuran pengetahuan mengenai faktor-faktor yang mempengaruhi kejadian BBLR. Hasil dari kegiatan pengabdian kepada masyarakat ini didapatkan setelah diberikan edukasi menggunakan poster seluruh ibu hamil sudah dapat menjelaskan mengenai pengertian dan faktor-faktor yang menyebabkan terjadinya BBLR